Laser removal of tattoo - a case report - Korabiusz, Katarzyna; Wawryków, Agata; Fabian-Danielewska, Anna; Stecko, Monika; Wilczyńska, Agnieszka; Janik-Fuks, Inga; Maciejewska, Martyna; Harasimowicz, Joanna (Journal of Education, Health and Sport, 2019)
Tattoo is one of the most frequently used techniques of permanent body decoration, it is a graphic sign obtained on the skin as a result of the introduction of dye into the skin tissue.It happens that the tattoo begins to disturb, life circumstances change, the tattoo reminds you of something you would like to forget. The development of tattoo removal methods is the expression of a search for a method to completely remove it without damaging the tissue. The methods used so far include: lasers, surgery, peels, dermabrasion (chemical and mechanical), cryosurgery, electrosurgery, light coagulation in the infrared range, salabrasia (use of sodium chloride), camouflage, etc., however, no method guarantees complete removal of the tattoo.